Waterbirds as cadmium sentinels in Brazil - Dos Santos Lima, Guilherme [UNESP]; Kamazuka, Silvia Harumi [UNESP]; Menegario, Amauri Antonio [UNESP]; Efe, Márcio Amorim (Instituto de Ecologia y Ciencias Ambientales (IECA), 2022)
Cadmium (Cd) is one of the most toxic elements of global concern in the environment with no biological value well known to science. Cadmium natural emissions, such as volcanic eruptions and natural fires, do not seem to release harmful concentrations of Cd in the environment, contrary to anthropogenic emissions (smelt, burning fossil fuels, phosphate fertilizer, nickel-cadmium batteries, plastic industry, etc). This review reports how waterbirds are used as sentinels of Cd concentrations on the Brazilian coast. We analyzed the standardization in methods and essential parameters to understand the levels and effects of Cd in this group of birds. Eighteen studies were carried out in the Brazilian territory, from 2007 to 2021, with a decline in publications in recent years. Cadmium concentrations were analyzed for 15 bird species, distributed in nine families and five orders. About 54% of the analyzed studies collected their samples in the territory of Rio de Janeiro state. Of the 17 Brazilian coastal states, Cd in waterbirds was only determined in eight states with the liver tissue being analyzed in 35% of the cases, followed by feathers (22%), kidney tissue (19%), muscles (13%), blood (8%), and eggshells (3%). In general, liver and kidney tissue concentrations were within the acceptable values for wild birds, 40 and 100 mg kg-1 respectively. Available data sets do not provide sufficient information to test any pattern of temporal and/or spatial trend in Cd concentrations in waterbirds. Besides, species of the same region do not necessarily concentrate the contaminants equally. Furthermore, the lack of standardization in methods and parameters compromises safe assessments of the conservation status of Brazilian waterbirds.
Aves aquáticas como sentinelas de cádmio no Brasil
Keywords: Bioaccumulation; Bioindicators; Contamination; Seabirds; Trace elements